2020
DOI: 10.1039/d0ta04250a
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the optical, electronic, and photoelectrochemical properties of p-type copper vanadate (p-Cu5V2O10) photocathodes

Abstract: Compact spray-pyrolysed Cu5V2O10 photocathodes with 1.9 eV bandgap show positive photocurrent onset voltage and promising photoresponse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…The peaks at 285, 349 and 522 cm À1 are assigned to the bending modes of the same structure, which is greatly in agreement with the Cu 5 V 2 O 10 crystal phase reported in a previous paper. 42 The Raman spectra further confirmed the successful preparation of CuV 2 O 6 , Cu 2 V 2 O 7 and Cu 5 V 2 O 10 , which was consistent with the XRD patterns. Fig.…”
Section: Morphology and Structure Of Copper Vanadatessupporting
confidence: 79%
“…The peaks at 285, 349 and 522 cm À1 are assigned to the bending modes of the same structure, which is greatly in agreement with the Cu 5 V 2 O 10 crystal phase reported in a previous paper. 42 The Raman spectra further confirmed the successful preparation of CuV 2 O 6 , Cu 2 V 2 O 7 and Cu 5 V 2 O 10 , which was consistent with the XRD patterns. Fig.…”
Section: Morphology and Structure Of Copper Vanadatessupporting
confidence: 79%
“…Regarding copper vanadates, Cu 3− x VO 4 was reported to have a narrow bandgap of 1.2 eV. [ 169 ] Recently, Song et al [ 170 ] reported thin film p‐type Cu 5 V 2 O 10 obtained by spray pyrolysis, having a bandgap of 1.8–2.0 eV. Moderate absorption properties and extensive charge trapping preventing the photogenerated carriers from reaching the interface are linked to the low photocurrents detected.…”
Section: Ternary Oxides As Photocathodesmentioning
confidence: 99%
“…16−21 In our previous work, we prepared β-Cu 2 V 2 O 7 and Cu 5 V 2 O 10 thin films using the spray pyrolysis method and demonstrated these mixed metal oxides as two promising photoelectrode candidates. 22,23 Jiang et al reported a γ-Cu 3 V 2 O 8 film with suitable band structure and excellent PEC stability and applied it as a photoanode for water electrolysis. 24 Cu 11 V 6 O 26 is another promising photoanode material for the water splitting reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ternary metal oxides have been widely applied as photoelectrodes for solar water splitting because of their relatively small band gap (1.8–2.1 eV) and good photostability in aqueous solutions. , Among them, copper vanadate photoelectrodes (α-CuV 2 O 6 , β-Cu 2 V 2 O 7 , γ-Cu 3 V 2 O 8 , Cu 5 V 2 O 10 , etc.) have attracted much attention for photoelectrochemical water splitting. In our previous work, we prepared β-Cu 2 V 2 O 7 and Cu 5 V 2 O 10 thin films using the spray pyrolysis method and demonstrated these mixed metal oxides as two promising photoelectrode candidates. , Jiang et al reported a γ-Cu 3 V 2 O 8 film with suitable band structure and excellent PEC stability and applied it as a photoanode for water electrolysis . Cu 11 V 6 O 26 is another promising photoanode material for the water splitting reaction.…”
Section: Introductionmentioning
confidence: 99%